Hydration in young water polo players: A bioelectrical impedance vector analysis (BIVA) approach - Sofia Serafini; Andrea Di Blasio; Iris Prestanti; Andrea Di Credico; Andrea Fusco; Jacopo Cilli; Gabriele Mascherini; Ruggero D'Anastasio; Pascal Izzicupo (Heliyon)
Purpose: This study aimed to assess hydration status before and after training using the bioelectrical impedance vector analysis (BIVA) method. Design: Pre-post quasi-experimental designs. Method: Twenty-four young water polo players (mean age: 13.30 ± 0.55) underwent assessment for bioelectrical and anthropometric measurements before and after a water polo training session. Results: Most players fell within the 50 % percentile of the bioelectrical tolerance ellipses of the reference population. The BIA vector differed statistically between players who achieved growth peaks (PGA: T2 = 9.1, p = 0.013) and those who did not (GPNA, T2 = 28.9, p < 0.001) compared to the reference and also differed between them (T2 = 37.7, p < 0.001). After training, a decrease in body mass (BM) and BM adjusted for water intake (p = 0.0001) and changes in BIA variables (p < 0.05) were observed. BIVA also showed a significant pre-post vector migration in both GPA (T2 = 24.7; p < 0.001) and GNPA (T2 = 43.1; p < 0.001), characterized by a decrease in resistance and opposite reactance directions (T2 = 33.6, p < 0.001). Conclusion: Young water polo players exhibit a significant BM loss after training (∼2.5 %). Ad libitum water intake seems to partially compensate dehydration. The resistance reduction indicates that BIVA captured the compensation for dehydration resulting from fluid intake.